2019
DOI: 10.1002/path.5252
|View full text |Cite
|
Sign up to set email alerts
|

F‐box protein FBXO16 functions as a tumor suppressor by attenuating nuclear β‐catenin function

Abstract: Aberrant activation of β‐catenin has been implicated in a variety of human diseases, including cancer. In spite of significant progress, the regulation of active Wnt/β‐catenin‐signaling pathways is still poorly understood. In this study, we show that F‐box protein 16 (FBXO16) is a putative tumor suppressor. It is a component of the SCF (SKP1‐Cullin1‐F‐box protein) complex, which targets the nuclear β‐catenin protein to facilitate proteasomal degradation through the 26S proteasome. FBXO16 interacts physically w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…FBXO16 interacts physically with the C-terminal domain of β-catenin and promotes its lysine 48-linked polyubiquitination and it can inhibit EMT by attenuating the level of β-catenin in BC cells [16]. This was consistent with our conclusion, the mRNA levels of FBXO16 were especially high in Luminal B subtypes and which was associated with better prognosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…FBXO16 interacts physically with the C-terminal domain of β-catenin and promotes its lysine 48-linked polyubiquitination and it can inhibit EMT by attenuating the level of β-catenin in BC cells [16]. This was consistent with our conclusion, the mRNA levels of FBXO16 were especially high in Luminal B subtypes and which was associated with better prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…Searching of novel tumor-related molecular markers is in full swing. As new cancer biomarkers, FBXO factors dysregulation have been reported in many cancers like BC, HCC, gastric cancer, ovarian carcinoma and osteosarcoma [7,9,10,16,42]. Although several FBXO family members have been con rmed to be related to BC, their distinct molecular mechanism remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functions of Fbxo16, Fbxo17, and Fbxw2 have all been linked to the regulation of the Wnt/β-catenin signaling pathway in non-muscle cells [ 153 , 154 , 155 , 156 , 157 , 158 ]. Fbxo27 was shown to direct damaged glycoproteins on the surface of lysosomes, including Lamp1 and Lamp2, towards autophagy-mediated degradation [ 159 ].…”
Section: The Role Of Cullin-1 Based Crls In Cross-striated Musclesmentioning
confidence: 99%
“…A20 plays an important role in inflammation and autoimmunity, but in 2017, Lee et al demonstrated its role in TGF-β1-induced EMT and metastasis of basal-like breast cancers, through multi-monoubiquitylation of Snail1 [ 143 ]. A recent study showed that Fbxo16 also promotes the lysine 48-linked polyubiquitination of β-catenin, and its further degradation in the proteasome machinery, thus inhibiting EMT and preventing malignancy [ 89 ]. Fbxo11 also induces the ubiquitination and degradation of Snail1 in a Pkd1 phosphorylation-dependent manner, also impacting on EMT.…”
Section: Emt Regulation By E3 Ubiquitin-ligasesmentioning
confidence: 99%